Role of funders in embedding tests in conservation practice - Rebecca K. Smith; Nancy Ockendon; Nida Al‐Fulaij; Alessandro Badalotti; Rachel Beattie; James Byrne; Sophia Cooke; Tiago de Zoeten; Winifred F. Frick; Stephan M. Funk; Douglas Gibbs; Lauren Gupta; et al. (Conservation Biology, 2026)
Effective conservation practice requires decisions based on reliable and relevant evidence, but significant gaps in the evidence base exist. Incorporating well‐designed tests of the effectiveness of interventions for biodiversity in conservation projects is one of the best ways to scale up the rate of evidence generation. Funders of conservation projects are uniquely positioned to support and incentivize such tests as part of the grant‐making process. Using a structured process, as 25 conservation funders and members of Conservation Evidence, we identified means of improving the effectiveness of the work funded through the support of enhanced evidence generation. We identified 11 approaches through which funders can support embedding testing, ranging from encouraging inclusion of a test in the project proposal, to designating separate funds for incorporating a test, to supporting an external testing unit to provide training and advice. The appropriate approaches vary depending on the scale, process, and type of funding. Barriers to supporting testing and potential solutions were discussed, barriers such as a lack of skills to check tests are appropriate and well designed and the additional time needed to develop, implement, and see outcomes of tests and differing types of projects. By encouraging testing of actions as part of conservation practice (where appropriate), funders will ultimately facilitate a stronger evidence base for more effective decision‐making and better outcomes for nature and society.

Globalism, localism and blue food systems – How can cross-scale tensions be reduced? A production perspective from UK seafood stakeholders - Alex J. Caveen; Bryce D. Stewart; Cameron Moffat; Daniel Skerritt; Estelle Jones; Huw Thomas; Lara Funk; Magnus Johnson; Mike Cohen; Michael Roach; Neil A. Auchterlonie; Samuel Peacock; et al. (Marine Policy, 2025)

P18-72 Integration of Metabolomics and Transcriptomics, as well as Mitostress, CALUX Assays and Targeted Proteomics for an Improved Mechanism-based Hazard Characterization of Drug-induced Liver Injury - F. Zickgraf; L. Wijaya; T. de Boer; C. Budin; S. Moco; V. Pozo Garcia; O. Pötz; P. Ternes; V. Giri; B. van de Water; C. Gomes; H. Kamp; et al. (Toxicology Letters, 2025)

P27-21 Inter-study reproducibility of plasma metabolomics data after 28-day treatment in rats – insights from the blinded ring trial MATCHING - F.M. Zickgraf; V. Haake; D. Funk-Weyer; H. Kamp (Toxicology Letters, 2025)

P18-103 Historical control database and acceptance criteria for a comparative in vitro hepatic enzyme assay(KaLy-Cell method) - S. Kellum; K. Choudhury; S. Melching-Kollmuss; A. Schafer; C. Parmentier; X. Sopko; L. Richert; H. Tinwell; C. Walter; I. Wohlman; F. Zhang; S. Catalano; et al. (Toxicology Letters, 2025)

P20-05 Polymer REACh on the horizon: technical challenges with polymer materials in several OECD test guideline methods addressing effects on human health and on biotic systems - S.N. Kolle; P. Demuth; N. Hambruch; N. Honarvar; S. Lüderwald; D. Funk-Weyer; R. Landsiedel (Toxicology Letters, 2024)

P13-29 A new mutagenicity NAM: An in vitro Transgenic Rodent (TGR) assay for the detection of mutagens and assessment of their mechanism of action - D. Funk-Weyer; R. Landsiedel; A. Göpfert; C. Rülker; M. Eichenlaub; B. Tokovenko; N. Honarvar; D. Schuster (Toxicology Letters, 2024)

P09-12 Thyroid hormones concentrations in cerebellum, cortex and whole-brain rat samples at certain life stages - C. Hindrichs; T. Walk; S. Melching-Kollmuss; R. Landsiedel; S. Schneider; H. Kamp; D. Funk-Weyer (Toxicology Letters, 2024)

P06-23 Integration of metabolomics and transcriptomics for improved mechanism-based hazard characterization of drug-induced liver injury - F.M. Zickgraf; L. Wijaya; T. de Boer; C. Budin; S. Moco; V. Pozo Garcia; P. Ternes; V. Giri; C. Gomes; B. van de Water; H. Kamp; D. Funk-Weyer (Toxicology Letters, 2024)

Novel rapid screening assay to incorporate complexity and increase throughput in early-stage plant biological testing - Sabrina M. Pittroff; Alexander R. Brems; Rune J. Brunshøj; Johan V. Christiansen; Emma Melgaard; Morten Lindqvist Hansen; David Llorente Corcoles; Jonathan Funk; Vilhelm K. Møller; Søren D. Petersen; Rasmus J.N. Frandsen; Niels B. Jensen; et al. (Rhizosphere, 2024)

Analysis of health concerns not addressed by REACH for low tonnage chemicals and opportunities for new approach methodology - Philip Botham; Mark T. D. Cronin; Richard Currie; John Doe; Dorothee Funk-Weyer; Timothy W. Gant; Marcel Leist; Sue Marty; Bennard van Ravenzwaay; Carl Westmoreland (Archives of Toxicology, 2023)
In Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) the criterion for deciding the studies that must be performed is the annual tonnage of the chemical manufactured or imported into the EU. The annual tonnage may be considered as a surrogate for levels of human exposure but this does not take into account the physico-chemical properties and use patterns that determine exposure. Chemicals are classified using data from REACH under areas of health concern covering effects on the skin and eye; sensitisation; acute, repeated and prolonged systemic exposure; effects on genetic material; carcinogenicity; and reproduction and development. We analysed the mandated study lists under REACH for each annual tonnage band in terms of the information they provide on each of the areas of health concern. Using the European Chemicals Agency (ECHA) REACH Registration data base of over 20,000 registered substances, we found that only 19% of registered substances have datasets on all areas of health concern. Information limited to acute exposure, sensitisation and genotoxicity was found for 62%. The analysis highlighted the shortfall of information mandated for substances in the lower tonnage bands. Deploying New Approach Methodologies (NAMs) at this lower tonnage band to assess health concerns which are currently not covered by REACH, such as repeat and extended exposure and carcinogenicity, would provide additional information and would be a way for registrants and regulators to gain experience in the use of NAMs. There are currently projects in Europe aiming to develop NAM-based assessment frameworks and they could find their first use in assessing low tonnage chemicals once confidence has been gained by their evaluation with data rich chemicals.

Conservation genomics of an endangered montane amphibian reveals low population structure, low genomic diversity and selection pressure from disease - D. R. Trumbo; B. M. Hardy; H. J. Crockett; E. Muths; B. R. Forester; R. G. Cheek; S. J. Zimmerman; S. Corey‐Rivas; L. L. Bailey; W. C. Funk (Molecular Ecology, 2023)
Wildlife diseases are a major global threat to biodiversity. Boreal toads ( Anaxyrus [Bufo] boreas ) are a state‐endangered species in the southern Rocky Mountains of Colorado and New Mexico, and a species of concern in Wyoming, largely due to lethal skin infections caused by the amphibian chytrid fungus Batrachochytrium dendrobatidis ( Bd ). We performed conservation and landscape genomic analyses using single nucleotide polymorphisms from double‐digest, restriction site‐associated DNA sequencing in combination with the development of the first boreal toad (and first North American toad) reference genome to investigate population structure, genomic diversity, landscape connectivity and adaptive divergence. Genomic diversity ( π = 0.00034–0.00040) and effective population sizes ( N e = 8.9–38.4) were low, likely due to post‐Pleistocene founder effects and Bd ‐related population crashes over the last three decades. Population structure was also low, likely due to formerly high connectivity among a higher density of geographically proximate populations. Boreal toad gene flow was facilitated by low precipitation, cold minimum temperatures, less tree canopy, low heat load and less urbanization. We found >8X more putatively adaptive loci related to Bd intensity than to all other environmental factors combined, and evidence for genes under selection related to immune response, heart development and regulation and skin function. These data suggest boreal toads in habitats with Bd have experienced stronger selection pressure from disease than from other, broad‐scale environmental variations. These findings can be used by managers to conserve and recover the species through actions including reintroduction and supplementation of populations that have declined due to Bd .

P22-44: In vitro – in vivo comparison of read-across approaches for phenoxy herbicides based on metabolome data from rat plasma and HepG2 cells - G. Caroline; F.M. Zickgraf; V. Giri; V. Haake; B. Birk; S. Sperber; H.-A. Huener; A. Verlohner; P. Driemert; T. Walk; D. Funk-Weyer; H. Kamp (Toxicology Letters, 2023)

P08-13: Analysis of Thyroid Hormone Metabolites in Rat Brain using an automated online-SPE-LC-MS/MS method - C. Hindrichs; T. Walk; S. Melching-Kollmuss; R. Landsiedel; H. Kamp; D. Funk-Weyer (Toxicology Letters, 2023)

Consensus Head Acceleration Measurement Practices (CHAMP): Study Design and Statistical Analysis - Steve Rowson; Jason Mihalik; Jillian Urban; Julianne Schmidt; Steve Marshall; Jaroslaw Harezlak; Brian D. Stemper; Mike McCrea; Jim Funk (Annals of Biomedical Engineering, 2022)
Head impact measurement devices enable opportunities to collect impact data directly from humans to study topics like concussion biomechanics, head impact exposure and its effects, and concussion risk reduction techniques in sports when paired with other relevant data. With recent advances in head impact measurement devices and cost-effective price points, more and more investigators are using them to study brain health questions. However, as the field's literature grows, the variance in study quality is apparent. This brief paper aims to provide a high-level set of key considerations for the design and analysis of head impact measurement studies that can help avoid flaws introduced by sampling biases, false data, missing data, and confounding factors. We discuss key points through four overarching themes: study design, operational management, data quality, and data analysis.

Consensus Head Acceleration Measurement Practices (CHAMP): Origins, Methods, Transparency and Disclosure - Kristy B. Arbogast; Jaclyn B. Caccese; Thomas A. Buckley; Andrew S. McIntosh; Kyvory Henderson; Brian D. Stemper; Gary Solomon; Steven P. Broglio; James R. Funk; Jeff R. Crandall (Annals of Biomedical Engineering, 2022)
The use of head kinematic measurement devices has recently proliferated owing to technology advances that make such measurement more feasible. In parallel, demand to understand the biomechanics of head impacts and injury in sports and the military has increased as the burden of such loading on the brain has received focused attention. As a result, the field has matured to the point of needing methodological guidelines to improve the rigor and consistency of research and reduce the risk of scientific bias. To this end, a diverse group of scientists undertook a comprehensive effort to define current best practices in head kinematic measurement, culminating in a series of manuscripts outlining consensus methodologies and companion summary statements. Summary statements were discussed, revised, and voted upon at the Consensus Head Acceleration Measurement Practices (CHAMP) Conference in March 2022. This manuscript summarizes the motivation and methods of the consensus process and introduces recommended reporting checklists to be used to increase transparency and rigor of future experimental design and publication of work in this field. The checklists provide an accessible means for researchers to apply the best practices summarized in the companion manuscripts when reporting studies utilizing head kinematic measurement in sport and military settings.

Correction to: Authors’ Reply to Letter to the Editor: Continued improvement to genetic diversity indicator for CBD - Linda Laikre; Paul A. Hohenlohe; Fred W. Allendorf; Laura D. Bertola; Martin F. Breed; Michael W. Bruford; W. Chris Funk; Gonzalo Gajardo; Antonio González-Rodríguez; Catherine E. Grueber; Philip W. Hedrick; Myriam Heuertz; et al. (Conservation Genetics, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s10592-021-01376-9

Authors’ Reply to Letter to the Editor: Continued improvement to genetic diversity indicator for CBD - Linda Laikre; Paul A. Hohenlohe; Fred W. Allendorf; Laura D. Bertola; Martin F. Breed; Michael W. Bruford; W. Chris Funk; Gonzalo Gajardo; Antonio González-Rodríguez; Catherine E. Grueber; Philip W. Hedrick; Myriam Heuertz; et al. (Conservation Genetics, 2021)

Comparison of Laboratory and On-Field Performance of American Football Helmets - Ann M. Bailey; Timothy L. McMurry; Joseph M. Cormier; James R. Funk; Jeff R. Crandall; Christina D. Mack; Barry S. Myers; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)

Why predict climate hazards if we need to understand impacts? Putting humans back into the drought equation - M. Enenkel; M. E. Brown; J. V. Vogt; J. L. McCarty; A. Reid Bell; D. Guha-Sapir; W. Dorigo; K. Vasilaky; M. Svoboda; R. Bonifacio; M. Anderson; C. Funk; et al. (Climatic Change, 2020)

Keys to enhancing the value of invasion ecology research for management - Jennifer L. Funk; Ingrid M. Parker; Virginia Matzek; S. Luke Flory; Erik T. Aschehoug; Carla M. D’Antonio; Wayne Dawson; Diane M. Thomson; Justin Valliere (Biological Invasions, 2020)

A search for new sources below 100 MeV in the Fermi-LAT data - G. Principe; D. Malyshev; J. Ballet; S. Funk (Rendiconti Lincei. Scienze Fisiche e Naturali, 2019)

Urbanization reduces genetic connectivity in bobcats ( Lynx rufus ) at both intra– and interpopulation spatial scales - Christopher P. Kozakiewicz; Christopher P. Burridge; W. Chris Funk; Patricia E. Salerno; Daryl R. Trumbo; Roderick B. Gagne; Erin E. Boydston; Robert N. Fisher; Lisa M. Lyren; Megan K. Jennings; Seth P. D. Riley; Laurel E. K. Serieys; et al. (Molecular Ecology, 2019)
Urbanization is a major factor driving habitat fragmentation and connectivity loss in wildlife. However, the impacts of urbanization on connectivity can vary among species and even populations due to differences in local landscape characteristics, and our ability to detect these relationships may depend on the spatial scale at which they are measured. Bobcats ( Lynx rufus ) are relatively sensitive to urbanization and the status of bobcat populations is an important indicator of connectivity in urban coastal southern California. We genotyped 271 bobcats at 13,520 SNP loci to conduct a replicated landscape resistance analysis in five genetically distinct populations. We tested urban and natural factors potentially influencing individual connectivity in each population separately, as well as study–wide. Overall, landscape genomic effects were most frequently detected at the study–wide spatial scale, with urban land cover (measured as impervious surface) having negative effects and topographic roughness having positive effects on gene flow. The negative effect of urban land cover on connectivity was also evident when populations were analyzed separately despite varying substantially in spatial area and the proportion of urban development, confirming a pervasive impact of urbanization largely independent of spatial scale. The effect of urban development was strongest in one population where stream habitat had been lost to development, suggesting that riparian corridors may help mitigate reduced connectivity in urbanizing areas. Our results demonstrate the importance of replicating landscape genetic analyses across populations and considering how landscape genetic effects may vary with spatial scale and local landscape structure.

Habitual nicotine-seeking in rats following limited training - A. Loughlin; D. Funk; K. Coen; A. D. Lê (Psychopharmacology, 2017)

Global resource acquisition patterns of invasive and native plant species do not hold at the regional scale in Mediterranean type ecosystems - Jennifer L. Funk; Monica A. Nguyen; Rachel J. Standish; William D. Stock; Fernando Valladares (Biological Invasions, 2017)

Effects of prazosin and doxazosin on yohimbine-induced reinstatement of alcohol seeking in rats - D. Funk; K. Coen; S. Tamadon; Z. Li; A. Loughlin; A. D. Lê (Psychopharmacology, 2016)

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

Plant functional traits of dominant native and invasive species in mediterranean‐climate ecosystems - Jennifer L. Funk; Rachel J. Standish; William D. Stock; Fernando Valladares (Ecology, 2016)
The idea that dominant invasive plant species outperform neighboring native species through higher rates of carbon assimilation and growth is supported by several analyses of global data sets. However, theory suggests that native and invasive species occurring in low‐resource environments will be functionally similar, as environmental factors restrict the range of observed physiological and morphological trait values. We measured resource‐use traits in native and invasive plant species across eight diverse vegetation communities distributed throughout the five mediterranean‐climate regions, which are drought prone and increasingly threatened by human activities, including the introduction of exotic species. Traits differed strongly across the five regions. In regions with functional differences between native and invasive species groups, invasive species displayed traits consistent with high resource acquisition; however, these patterns were largely attributable to differences in life form. We found that species invading mediterranean‐climate regions were more likely to be annual than perennial: three of the five regions were dominated by native woody species and invasive annuals. These results suggest that trait differences between native and invasive species are context dependent and will vary across vegetation communities. Native and invasive species within annual and perennial groups had similar patterns of carbon assimilation and resource use, which contradicts the widespread idea that invasive species optimize resource acquisition rather than resource conservation.

Arginase-1 deficiency - Yuan Yan Sin; Garrett Baron; Andreas Schulze; Colin D. Funk (Journal of Molecular Medicine, 2015)

Lagged effects of early-season herbivores on valley oak fecundity - Ian S. Pearse; Kyle A. Funk; Thomas S. Kraft; Walter D. Koenig (Oecologia, 2015)

Pollen limitation and flower abortion in a wind‐pollinated, masting tree - Ian S. Pearse; Walter D. Koenig; Kyle A. Funk; Mario B. Pesendorfer (Ecology, 2015)
Pollen limitation is a key assumption of theories that explain mast seeding, which is common among wind‐pollinated and woody plants. In particular, the pollen coupling hypothesis and pollination Moran effect hypothesis assume pollen limitation as a factor that synchronizes seed crops across individuals. The existence of pollen limitation has not, however, been unambiguously demonstrated in wind‐pollinated, masting trees. We conducted a two‐year pollen supplementation experiment on a masting oak species, Quercus lobata . Supplemental pollen increased acorn set in one year but not in the other, supporting the importance of pollen coupling and pollination Moran effect models of mast seeding. We also tracked the fate of female flowers over five years and found that the vast majority of flowers were aborted for reasons unrelated to pollination, even in the presence of excess pollen. Pollen limitation can reduce annual seed set in a wind‐pollinated tree, but factors other than pollen limitation cause the majority of flower abortion.

Operant self-administration of alcohol and nicotine in a preclinical model of co-abuse - A. D. Lê; Douglas Funk; Steven Lo; Kathleen Coen (Psychopharmacology, 2014)

Effects of stressors on the reinforcing efficacy of nicotine in adolescent and adult rats - Sheng Zou; Douglas Funk; Megan J. Shram; A. D. Lê (Psychopharmacology, 2014)

Dietary (periphyton) and aqueous Zn bioaccumulation dynamics in the mayfly Centroptilum triangulifer - K. S. Kim; D. H. Funk; D. B. Buchwalter (Ecotoxicology, 2012)

Testing a high-resolution satellite interpretation technique for crop area monitoring in developing countries - M. T. Marshall; G. J. Husak; J. Michaelsen; C. Funk; D. Pedreros; A. Adoum (International Journal of Remote Sensing, 2011)

Effect of prazosin and guanfacine on stress-induced reinstatement of alcohol and food seeking in rats - A. D. Lê; Douglas Funk; Walter Juzytsch; Kathleen Coen; Brittany M. Navarre; Carlo Cifani; Yavin Shaham (Psychopharmacology, 2011)

Food rationing affects dietary selenium bioaccumulation and life cycle performance in the mayfly Centroptilum triangulifer - J. M. Conley; D. H. Funk; N. J. Cariello; D. B. Buchwalter (Ecotoxicology, 2011)

Investigations into the status of a new taxon of Salanoia (Mammalia: Carnivora: Eupleridae) from the marshes of Lac Alaotra, Madagascar - Joanna Durbin; Stephan M. Funk; Frank Hawkins; Daphne M. Hills; Paulina D. Jenkins; Clive B. Moncrieff; Fidimalala Bruno Ralainasolo (Systematics and Biodiversity, 2010)

Evidence for recent population bottlenecks in northern spotted owls (Strix occidentalis caurina) - W. Chris Funk; Eric D. Forsman; Matthew Johnson; Thomas D. Mullins; Susan M. Haig (Conservation Genetics, 2010)

Coadministration of intravenous nicotine and oral alcohol in rats - A. D. Lê; Steven Lo; Stephen Harding; Walter Juzytsch; Peter W. Marinelli; Douglas Funk (Psychopharmacology, 2010)

The CRF1 receptor antagonist antalarmin attenuates yohimbine-induced increases in operant alcohol self-administration and reinstatement of alcohol seeking in rats - Peter W. Marinelli; Douglas Funk; Walter Juzytsch; Stephen Harding; Kenner C. Rice; Yavin Shaham; A. D. Lê (Psychopharmacology, 2007)

Conservation genetics of snowy plovers (Charadrius alexandrinus) in the Western Hemisphere: population genetic structure and delineation of subspecies - W. Chris Funk; Thomas D. Mullins; Susan M. Haig (Conservation Genetics, 2007)

Molecular Phylogenetic Relationships Among Crested-tailed Mice (Genus Habromys) - Duke S. Rogers; Christopher C. Funk; Jacqueline R. Miller; Mark D. Engstrom (Journal of Mammalian Evolution, 2007)

Periadolescent and adult rats respond differently in tests measuring the rewarding and aversive effects of nicotine - Megan J. Shram; Douglas Funk; Zhaoxia Li; Anh D. Lê (Psychopharmacology, 2006)

Effects of unconditioned and conditioned social defeat on alcohol self-administration and reinstatement of alcohol seeking in rats - D. Funk; S. Harding; W. Juzytsch; A. D. Lê (Psychopharmacology, 2005)

PAQR Proteins: A Novel Membrane Receptor Family Defined by an Ancient7-Transmembrane Pass Motif - Y. Tom Tang; Tianhua Hu; Matthew Arterburn; Bryan Boyle; Jessica M. Bright; Peter C. Emtage; Walter D. Funk (Journal of Molecular Evolution, 2005)

Role of alpha-2 adrenoceptors in stress-induced reinstatement of alcohol seeking and alcohol self-administration in rats - A. D. L; S. Harding; W. Juzytsch; D. Funk; Y. Shaham (Psychopharmacology, 2005)

Influence of stressors on the rewarding effects of alcohol in Wistar rats: studies with alcohol deprivation and place conditioning - D. Funk; S. Vohra; A. D. L (Psychopharmacology, 2004)

Augmented responses to morphine and cocaine in mice with a 12-lipoxygenase gene disruption - Carrie L. Walters; Bao-Cheng Wang; Misty Godfrey; Duxin Sun; Colin D. Funk; Julie A. Blendy (Psychopharmacology, 2003)

The relationship between flesh quality and numbers of Kudoa thyrsites plasmodia and spores in farmed Atlantic salmon, Salmo salar L. - J A Dawson‐Coates; J C Chase; V Funk; M H Booy; L R Haines; C L Falkenberg; D J Whitaker; R W Olafson; T W Pearson (Journal of Fish Diseases, 2003)
Atlantic salmon, Salmo salar L., were exposed to Kudoa thyrsites (Myxozoa, Myxosporea)‐containing sea water for 15 months, and then harvested and assessed for parasite burden and fillet quality. At harvest, parasites were enumerated in muscle samples from a variety of somatic and opercular sites, and mean counts were determined for each fish. After 6 days storage at 4 °C, fillet quality was determined by visual assessment and by analysis of muscle firmness using a texture analyzer. Fillet quality could best be predicted by determining mean parasite numbers and spore counts in all eight tissue samples (somatic and opercular) or in four fillet samples, as the counts from opercular samples alone showed greater variability and thus decreased reliability. The variability in both plasmodia and spore numbers between tissue samples taken from an individual fish indicated that the parasites were not uniformly distributed in the somatic musculature. Therefore, to best predict the probable level of fillet degradation caused by K. thyrsites infections, multiple samples must be taken from each fish. If this is performed, a mean plasmodia count of 0.3 mm −2 or a mean spore count of 4.0 × 10 5 g −1 of tissue are the levels where the probability of severe myoliquefaction becomes a significant risk.

Erratum: Periodic carbon flushing to roots of Quercus rubra saplings affects soil respiration and rhizosphere microbial biomass - Zoe G. Cardon; Andrew D. Czaja; Jennifer L. Funk; Pati L. Vitt (Oecologia, 2002)

Periodic carbon flushing to roots of Quercus rubra saplings affects soil respiration and rhizosphere microbial biomass - Zoe G. Cardon; Andrew D. Czaja; Jennifer L. Funk; Pati L. Vitt (Oecologia, 2002)

Role of central dopaminergic and 5-hydroxytryptaminergic projections in the behavioral responses elicited by thyrotropin-releasing hormone in rats - D. Funk; R. M. Post; A. Pert (Psychopharmacology, 1997)

Neuropathology of organophosphate-induced delayed neuropathy (OPIDN) in young chicks - Kathleen A. Funk; John D. Henderson; Chen-Hsuan Liu; Robert J. Higgins; Barry W. Wilson (Archives of Toxicology, 1994)